ENSURING THE QUALITY OF BUSINESS PROCESSES IN THE THREECLUSTER GSI-MODEL OF AN INNOVATION ENTREPRENEURSHIP ECOSYSTEM - RIEPINA, Inna; YAKUSHEVA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the quality assurance of business processes in the threecluster GSI-model of the innovative entrepreneurship ecosystem. Effective functioning of innovative entrepreneurship in Ukraine will ensure the implementation of its ecosystem model, which will improve the functioning and development of ecosystem entities based on ensuring the quality of its business processes. The paper proposes a threecluster GSI-model of the innovative entrepreneurship ecosystem, the implementation of which will ensure the sustainable development of innovative entrepreneurship in Ukraine thanks to the implementation of its components. Cluster G (generation) will ensure the generation of business ideas, cluster S (support) aims to support the development of innovative entrepreneurship, cluster I (implementation) implements developed innovative ideas. The article proposes a number of measures, the implementation of which will have a positive impact on the development of innovative entrepreneurship in Ukraine and the formation of its ecosystem. The basis of the development of innovative entrepreneurship is knowledge, science, intellectual capital and the high-tech sector of the economy. The implementation of the proposed measures in each GSI-model cluster will have a positive impact on the quality of business processes of the ecosystem of innovative entrepreneurship from the generation of a business idea to its implementation and commercialization. The effectiveness of business processes will depend on the creation of business ideas focused on the needs of consumers to their rapid implementation on the market and creation of value for consumers. The implementation of this model will significantly increase the functioning and development of innovative entrepreneurship, which will ensure an increase in competitive positions on the global market.